Uveal Effusion Syndrome: Clinical Characteristics, Outcome of Surgical Treatment, and Histopathological Examination of the Sclera - Zhou, Nan; Yang, Lihong; Xu, Xiaolin; Wei, Wenbin (Frontiers in Medicine, 2022)
Purpose In this study, we aimed to investigate clinical characteristics and histopathology and evaluate surgical outcomes of quadrantic lamellar-sclerectomy with sclerostomy for uveal effusion syndrome (UES). Design Retrospective, cohort study. Participants Overall, 106 eyes of 66 patients diagnosed with UES were treated at the Beijing Tongren Hospital between January 1, 2001 and June 26, 2021. Methods Patients were examined by routine ophthalmologic examinations, fluorescein and indocyanine green angiography (FFA/ICGA); axial length determination; color Doppler ultrasound (CDU); ultrasound biomicroscopy (UBM), optical coherence tomography (OCT), and optical coherence tomographic angiography (SD/SS-OCTA). Quadrantic lamellar-sclerectomy with sclerostomy was performed at the equator in all patients and histopathological examination of the excised sclera was analyzed in all samples. Main Outcome Measures The reattachment of the choroid and retina with resolution of the serous fluid, best corrected visual acuity (BCVA), choroidal thickness, and recurrence of ciliochoroidal detachment were the main outcome measures. Results Two subgroups were identified: (1) type 1 (nanophthalmic eye), wherein the eyeball was small (average axial length 15.83 ± 1.45 mm) with high hypermetropia (average 12.6 diopters) and (2) type 2 (non-nanophthalmic eye), wherein the eyeball size was normal (average axial length 23.45 ± 1.68 mm) with or without refractive error, combined with or without systemic symptoms. Histopathologically, types 1 and 2 demonstrated similarly abnormal sclera with the disorganization of collagen fiber bundles and deposits of proteoglycans in the matrix. Quadrantic lamellar-sclerectomy with sclerostomy was effective in both types 1 and 2, inducing post-operative resolution of the subretinal fluid accumulation and increasing the useful BCVA. The choroidal thickness was significantly different before and after surgery (P < 0.05). Approximately 98.1% of cases attained permanent reattachment within 6 months after one operation through this procedure. The single operation success rate was 96.2%, and success with one or two operations was 100%. Conclusions UES is caused by abnormalities of the sclera and increased resistance to transscleral fluid outflow, combined with increased choroidal thickness. Quadrantic lamellar-sclerectomy with sclerostomy is an effective treatment for UES that can rescue correct the useful visual acuity.